Pollution levels and risks of polycyclic aromatic hydrocarbons in surface sediments from two typical estuaries in China. Issue 2 (30th January 2017) - Wang, Chenglong; Zou, Xinqing; Li, Yali; Zhao, Yifei; Song, Qiaochu; Yu, Wenwen
Abstract: To assess the environmental risks of polycyclic aromatic hydrocarbons (PAHs), 48 and 45 sediments were collected from the Yangtze River Estuary (YRE) and Pearl River Estuary (PRE), respectively. The toxicity equivalency concentration (TEQ) in the YRE and PRE were ranged from 1.68 to 76.13 and 9.28 to 129.24 ng TEQ g − 1, respectively. Results of risk quotient suggest that ecological risks of two estuaries are at a moderate level, but are higher in the PRE than YRE. The increment lifetime cancer risks (ILCR) from the YRE via ingestion and dermal contact were 1 × 10 − 6 to 5.6 × 10 − 5 and 4 × 10 − 6 to 1.6 × 10 − 4, and ranged from 7 × 10 − 6 to 9.4 × 10 − 5 and 2 × 10 − 5 to 2.8 × 10 − 4 in the PRE. ILCR results suggest that some low and moderate cancer risk exists in the YRE and PRE. Therefore, monitoring and control measures should be carried out immediately to reduce or eliminate the risks to human health from environmental exposure. Graphical abstract: Highlights: Polycyclic aromatic hydrocarbons (PAHs) cause environmental and human health risks. We compared PAHs in sediment from the Yangtze (YRE) and Pearl River Estuaries (PRE). Ecological risks in both estuaries are moderate, and higher in PRE than YRE. Risk of cancer from contact with the sediment is low to moderate in both estuaries. Control measures should be carried out to reduce or eliminate these risks.